Nilai-Nilai Pendidikan Islam Dalam Budaya Sekolah MIS Miftahul Khoir Rasau Jaya Kubu Raya - Muhammad Basarrudin (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
The purpose in this study was to provide an explanation of the implementation of school culture at MIS Miftahul Khoir and explain any Islamic education values present in the school culture of MIS Miftahul Khoir. This research used descriptive qualitative research type. In this research using qualitative method with descriptive research type. Data collection techniques used observation, interviews, and documentation. Data were analyzed by reducing, presenting, and drawing conclusions. The results showed that the school culture currently implemented at MIS Miftahul Khoir is a learning program to read the Qur'an, dhuha prayer in congregation, tahfidz program every day at 05.30, reading juz amma together at 06. 15, jariyah (shodaqoh) which is done every Friday, yasinan around which is done every Friday and Saturday, habituation to wear Muslim clothes in the 2nd and 4th week every Friday, every Friday of the 4th week, student guardians hold istighosah, muharrom parade and orphan compensation every new hijriyyah year, halal bi halal every 5th to 6th of Shawwal, where students are asked to visit the teacher's house, Eid al-Qurban, and other PHBI (commemoration of Islamic holidays) activities such as maulid nabi. This research not only makes a theoretical contribution to Islamic education literature but also offers relevant practical guidance to improve the quality of religious values-based education in schools